Towards a proof theory for Henkin quantifiers. (5th January 2021) - Baaz, Matthias; Lolic, Anela
Abstract: This paper presents a methodology to construct globally sound but possibly locally unsound analytic calculi for partial theories of Henkin quantifiers. It is demonstrated that usual locally sound analytic calculi do not exist for any reasonable fragment of the full theory of Henkin quantifiers. This is due to the combination of strong and weak quantifier inferences in one quantifier rule.